Dufour and Soret effects on steady MHD free convection and mass transfer fluid flow through a porous medum in a rotating system - Islam, Nazmul; Alam, Md Mahmud (Journal of Naval Architecture and Marine Engineering, 2008)
The numerical studies are performed to examine the steady MHD free convection and mass transfer fluid flow through a continuously moving porous medium with thermal diffusion and diffusion thermo past a semi-infinite vertical porous plate in a rotating system. Impulsively started plate moving in its own plane is considered. With appropriate transformations the boundary layer equations are transformed into nonlinear ordinary differential equations. The local similarity solutions of the transformed dimensionless equations for the flow, heat and mass transfer characteristics are evaluated using shooting iteration technique. Numerical results are presented in the form of velocity, temperature and concentration within the boundary layer for different parameters entering into the analysis. Also the effects of the pertinent parameters on the local skin-friction coefficients and rate of heat transfer as well as rate of mass transfer in terms of the local Nusselt number and Sherwood number respectively are also discussed. Keywords: MHD free convection, porous medium, rotation effect, Dufour effect, Soret effect. DOI: 10.3329/jname.v4i1.915 Journal of Naval Architecture and Marine Engineering 4(2007) 43-55